(untitled) (Economic and Political Thought, 2014)
The financial crisis has had a significant influence on the European and the US banking sector. The results of the analysis show that as a result of the crisis the size of the banking component of the most developed financial systems has decreased. At the same time, cross-border expansion has lost its importance. The concentration level has ceased to rise in the European Union, and economic efficiency is subject to significant volatility. In this context, it should be noted that the process of creating a single market for financial services is far from being completed in the European Union. The evolu tion of the US banking sector bears some similarity to the performance of the European banks, however credit institutions in the US have better financial results.